ASEAN Non-Interference Under Heavy Pressure: Is It Change or Crises for ASEAN Peace? - Spastyono, Jeko; Malik, Ichsan; Wahyudi, Bambang (Universitas Airlangga, 2024)
This paper intends to join the discussion over the heavily pressured ASEAN's non- interference. With a qualitative approach, this paper investigate where the pressure comes from and whether non-interference actually harms ASEAN. Utilizing the medical analogy,